Computational evaluation of bioactive compounds in Curcuma zanthorrhiza targeting SIRT1 and NFκB - Sasangka Prasetyawan; Anna Safitri; Mochammad Fitri Atho'illah; Sri Rahayu (BioTechnologia, 2023)
Type 2 diabetes mellitus (T2DM) is a metabolic disease with a high risk of complications and mortality. Novel T2DM therapeutic interventions are needed to combat this disease. This study aimed to identify pathways in¬vol¬ved in T2DM and investigate sesquiterpenoid compounds from Curcuma zanthorrhiza that could act as SIRT1 activators and NFκB inhibitors. Protein–protein interaction and bioactive compound analysis were conducted using the STRING and STITCH databases, respectively. Molecular docking was used to determine the compounds’ interactions with SIRT1 and NFκB, while toxicity prediction was performed using Protox II. The results showed that curcumin could act as a SIRT1 activator (4I5I, 4ZZJ, and 5BTR) and NFκB inhibitor on the p52 relB complex and p50–p65 heterodimer, while xanthorrhizol could function as an IκK inhibitor. The toxicity prediction indicated that the active compounds of C. zanthorrhiza were relatively nontoxic because beta-curcumene, curcumin, and xanthorrizol belong to toxicity classes 4 or 5. These findings suggest that the bioactive compounds of C. zanthorrhiza could be promising candidates for developing SIRT1 activators and NFκB inhibitors to combat T2DM.